An overview of randomization techniques: An unbiased assessment of outcome in clinical research - K P Suresh (Wolters Kluwer Medknow Publications, 2011)
Randomization as a method of experimental control has been extensively used in human clinical trials and other biological experiments. It prevents the selection bias and insures against the accidental bias. It produces the comparable groups and eliminates the source of bias in treatment assignments. Finally, it permits the use of probability theory to express the likelihood of chance as a source for the difference of end outcome. This paper discusses the different methods of randomization and use of online statistical computing web programming (www.graphpad.com/quickcalcs or www.randomization.com) to generate the randomization schedule. Issues related to randomization are also discussed in this paper.